The Longest Voyage : Circumnavigators in the Age of Discovery - Silverberg, Robert (Book collections on Project MUSE., 2020)
Capturing the total context of political climate and historical change that made the Age of Discovery one of excitement and drama, Silverberg brings a motley crew of early ocean explorers vividly to life.